2007
DOI: 10.1055/s-2007-970554
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Probability of Meningioma Recurrence in the Preoperative and Early Postoperative Period: A Multivariate Analysis in the Midterm Follow-Up

Abstract: We reviewed the clinical, radiological, surgical, and histopathological features of patients with meningiomas to identify factors that can predict tumor recurrence after ''microscopic total removal,'' to improve preoperative surgical planning, and to help determine the need for close radiological observation at shorter intervals or the need for radiotherapy as an adjuvant treatment in the early postoperative period. Clinical data, magnetic resonance imaging studies, angiographic data, operative reports, and hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 28 publications
6
66
1
1
Order By: Relevance
“…14,18 The recurrence rate has also been described as higher for males when all histopathological grades of intracranial meningiomas were considered. 13 However, similar observation for spinal meningiomas is not available in the literature, presumably due to fewer reported recurrences. A dural tail can be present in up to half of the cases of spinal meningiomas.…”
Section: Tumor Recurrencementioning
confidence: 90%
“…14,18 The recurrence rate has also been described as higher for males when all histopathological grades of intracranial meningiomas were considered. 13 However, similar observation for spinal meningiomas is not available in the literature, presumably due to fewer reported recurrences. A dural tail can be present in up to half of the cases of spinal meningiomas.…”
Section: Tumor Recurrencementioning
confidence: 90%
“…5,6 Several groups have investigated the prognostic significance of baseline HQOL parameters and baseline clinical characteristics for clinical outcome. [7][8][9][10] In these studies, a variety of unspecialized HQOL instruments were used to evaluate global HQOL after meningioma resection. However, it is not sufficient to describe the relationship between meningioma and HQOL in global terms.…”
Section: Introductionmentioning
confidence: 99%
“…Ilidian et al, 9 reported that age and gender has no influence on proliferative activity. Kasuya et al 10 reported that male gender was an independent risk factor for high proliferative potential.…”
Section: Discussionmentioning
confidence: 99%